Social networks consumption in Ecuador An exploratory survey in Riobamba and Quito (2013 – 14) - Barredo Ibáñez, Daniel (2014)
Digital communication in Ecuador is relatively differentiated particularly as a consequence of the low Internet connection rate in the Andean Republic According to official figures, in 2013 just four out of ten Ecuadorians had network connection. In addition, the communication context is in the middle of an interesting transformation process through the approval of instruments like the Communication Organic Law in 2013, which despite its exhaustive nature it does not regulate the communication contents issued by social network users.This article, through a survey targeted to citizens of two of the main cities of the country -Quito and Riobamba- intends to explore and determine how people living in these urban sites use social networks, and the possible age differences. The results indicate that YouTube, Facebook and Google are the social networks mostly used by Ecuadorians. In addition, after establishing that the major focus was on conventional social networks and iconic trends and those that allowed a mainly interpersonal use, the intergenerational and interprovincial gap was confirmed.